2012
DOI: 10.1097/adm.0b013e3182541933
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Substance Abuse Program for Opioid-Dependent Nonurban Pregnant Women Improves Outcome

Abstract: Improved access to opioid agonist treatment programs for the general population in nonurban areas improves perinatal outcome and retention of maternal guardianship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Consistent with previous studies, this multiyear population-based study found an increasing prevalence of opioids use/abuse among pregnant women in the US [1, 35, 7, 10, 17, 25, 26]. In our previous investigation of national trends of opioid use among pregnant mothers in the US, we discuss the alarming overall increase, as well as geographic, regional, and sociodemographic differences in both the rate and trends of opioid use over 12 years [16].…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies, this multiyear population-based study found an increasing prevalence of opioids use/abuse among pregnant women in the US [1, 35, 7, 10, 17, 25, 26]. In our previous investigation of national trends of opioid use among pregnant mothers in the US, we discuss the alarming overall increase, as well as geographic, regional, and sociodemographic differences in both the rate and trends of opioid use over 12 years [16].…”
Section: Discussionsupporting
confidence: 90%
“…Throughout the study period, there were 9 WV federally funded opioid maintenance therapy (OMT) facilities that accepted pregnant women for the recommended OMT treatment, of which only 1 was located in the southeastern area of WV (Figure ) . Although OMT can result in NAS, the therapy is preferred over continued illegal substance use in order to improve obstetric and neonatal outcomes via decreased maternal illicit behaviors, improved prenatal care, and elimination of acute intoxication and withdrawal during pregnancy . Therefore, higher regional occurrence of adverse obstetric and neonatal health outcomes could be linked to the lack of available treatment options for this vulnerable population …”
Section: Discussionmentioning
confidence: 99%
“…Drug or alcohol use during pregnancy can have a negative impact medically and socially on both the mother and newborn (Shankaran et al, 2007;Terplan & Wright, 2011). Integrated treatment during pregnancy as well as early intervention for the newborn can ameliorate these negative effects (Meyer et al, 2012;Niccols et al, 2012;Peadon, Rhys-Jones, Bower, & Elliott, 2009).…”
Section: Recent Amendments To the Child Abuse Prevention And Treatmentmentioning
confidence: 98%